Effect of Hydrofoil Angle of Attack on Resistance Reduction and Lift Generation in a Planing Hull - M Daffa Nafis Shafwan; Kurniawan Teguh Waskito (International Journal of Marine Engineering Innovation and Research, 2026)
Abstract¾Hydrodynamic resistance remains a key factor governing the performance of high-speed planing vessels, as it directly determines propulsion power requirements. Despite extensive studies on hydrofoil performance, the application of the NACA 6409 profile in planing hull vessels remains limited. In particular, its potential as a fixed hydrofoil configuration, which may reduce design complexity and enhance practical implementation, has not been thoroughly investigated. Therefore, this study aims to evaluate the effect of hydrofoil angle of attack on resistance reduction and lift generation in a small planing hull vessel. Numerical simulations were conducted using Computational Fluid Dynamics (CFD) in ANSYS Fluent with the SST k–ω turbulence model. Angles of attack of 0°, 5°, 10°, and 15° were analyzed at operating speeds of 15 and 20 knots under foilborne conditions. The results show that low angles of attack, particularly 0° and 5°, provide the greatest resistance reduction, achieving up to 63.3% lower total resistance compared to the non-hydrofoil configuration at 20 knots. In contrast, higher angles of attack (≥10°) increase resistance due to induced drag and flow separation. The hydrofoil configuration also reduces propulsion power requirements and enables foilborne operation at speeds above 15 knots with a minimum angle of attack of 5°. These findings identify the optimal operating range of the NACA 6409 hydrofoil and provide practical design guidance for improving the efficiency of hydrofoil-assisted planing vessels.